Comparing the integral characteristics of secondary droplet atomization under different situations; International Communications in Heat and Mass Transfer; Vol. 108 - Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich; Tarlet D. Dominique; Bellettre J. Jerome (2019, 2019)
Title screen